Manajemen Kurikulum Program Pembelajaran Kewirausahaan di Sekolah Menengah Kejuruan - Zahrotun Ni’mah Afif (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2024)
This research examines the planning, implementation and supervision of the entrepreneurship learning program at the Cukir Diwek Jombang Muallimat College Vocational School. The aim of this research is to evaluate how curriculum planning is carried out, how learning programs are implemented, and how supervision of these programs is carried out. This research uses a qualitative approach with a case study method. Data collection was carried out through interviews, observation and documentation of school principals, curriculum cadets and field teachers. The research results show that entrepreneurship curriculum planning is carried out comprehensively by involving various stakeholders, ensuring the curriculum is relevant and in line with the needs of the job market. Implementation of the program uses experiential learning methods, combining theory and direct practice, as well as collaboration with local industry, although it still requires improvements in the use of technology and ongoing training for teachers. Supervision is carried out through academic and non-academic approaches, ensuring the achievement of educational goals and the development of students' practical skills. In conclusion, the entrepreneurship learning program at the Jombang Muallimat Vocational School is effective in equipping students with the necessary entrepreneurial skills, but requires several improvements to achieve more optimal results